Droplet impact on a thin fluid layer - Howison, S; Ockendon, J; Oliver, J; Purvis, R; Smith, F (2005)
The initial stages of high-velocity droplet impact on a shallow water layer are described, with special emphasis given to the spray jet mechanics. Four stages of impact are delineated, with appropriate scalings, and the successively more important influence of the base is analysed. In particular, there is a finite time before which part of the water in the layer remains under the droplet and after which all of the layer is ejected in the splash jet.